How art-as-therapy supports participants with a diagnosis of schizophrenia : a phenomenological investigation - Mitchell, Julia L G (Rhodes University, Faculty of Humanities, Department of Psychology, 2021)
Although art therapy is recommended in management programmes for individuals with a diagnosis of schizophrenia, calls have been made for more detailed explanations as to how artmaking is working. This study responds to those calls by considering the artmaking experiences of 15 mental health users with a diagnosis of schizophrenia, resident at a forensic, mental health facility in South Africa. A phenomenological approach was chosen because of its focus on lived experiences, suited to explore the embodied and pre-reflective experience of studio-based artmaking. Dialogical and narrative understandings were subsequently incorporated to account for more reflective aspects of the artmaking experience. Two main participant descriptions of artmaking, centring on feeling at home and on doing something meaningful, guided the phenomenological lifeworld method in analysing the data (interviews, artworks and field observations in art groups and exhibitions), along selected dimensions of lived experience, namely embodiment, temporality, spatiality, sociality and selfhood. These findings lend support to new phenomenological research which suggests that artmaking intersects with disrupted abilities for perceptual engagement underlying manifestations of schizophrenia symptomology. This research supports assertions that artmaking has the potential to support the minimal sense of self and expand possibilities for renewed embodied and more reflective meaning-making. Explanations of findings centred around the distinct artistic style of each participant, as well as their artworks which revealed individual lifeworlds including a variety of self-positions. The inherent properties of the completed artworks also provided possibilities for renewed experiences of sociality. Additional support for the findings is drawn from recent research in the fields of early neurodevelopmental trauma, and trauma research findings within the art therapy field.
Keywords: Schizophrenia -- Treatment; Schizophrenia -- Treatment -- South Africa -- Case studies; Art Therapy; Art Therapy -- South Africa -- Case studies; Stormberg Hospital (Eastern Cape, -- South Africa)